Understanding domestic consumer attitude and behaviour towards energy: A study on the Island of Ireland - Caulfield, Brian (My University, 2023)
Attitudes towards renewable technologies and knowledge about energy consumption influences the adoption of sustainable energy systems across power, heat and transport. Research suggests that behavioural change strategies could accelerate the transition towards net-zero by reducing household energy consumption, increasing the uptake of energy efficient technologies and optimising consumption patterns. In tandem, emerging markets and business models facilitated by energy decentralisation and digitalisation give consumers more control over their home energy management and adopt more energy efficient behaviours. This empirical study seeks to determine the level of awareness of domestic consumers on the island of Ireland, which makes for an interesting case study due to the existence of a single electricity market with a dichotomic regulatory regime. This survey is critical to engineers, industry and other stakeholders in understanding the implications of climate policy aspirations and targets as society transitions towards carbon neutrality. A questionnaire was issued to a sample of 1,373 respondents in March 2022, facilitated by a third-party survey provider. The questionnaire had 40 questions composed of multiple-choice and single-answer format; questions covered participants’ sociodemographic attributes, their willingness to adopt new technologies and services and their eco-credentials. The results identify the strengths, weaknesses and opportunities for householders to adopt more efficient household energy behaviours and attitudes towards smart energy technology and their carbon footprint. This study explores the emerging, yet significant role of domestic consumers in an equitable transition to a sustainable future.
PUBLISHED
Keywords: Energy survey; Domestic consumer; Ireland; Northern Ireland; Net-zero transition; Inclusive Society; Smart & Sustainable Planet; Environmental aspects of transportation; Transport